ANALISIS TEKNIK DAN KUALITAS TERJEMAHAN ISTILAH BUDAYA DALAM KUMPULAN ABSTRAK HASIL PENELITIAN SEKOLAH TINGGI SENI INDONESIA (STSI) SURAKARTA - Dewi Nurnani; M.R. Nababan; D. Djatmika (Universitas Sebelas Maret, 2018)
The aims of the study are to ascertain (1) translation techniques applied in Kumpulan Abstrak Hasil Penelitian 1990-1991 Sekolah Tinggi Seni Indonesia (STSI) Surakarta; (2) the character of translation techniques applied in the translation of Kumpulan Abstrak Hasil Penelitian 1990-1991 Sekolah Tinggi Seni Indonesia (STSI) Surakarta ; and (3) levels of translation accuracy and acceptability and their relationships with the techniques as well as character of translation techniques. This is a descriptive qualitative research with an embedded-case study in translation which uses purposive sampling technique. The sources of data for this research method comprise of a document of Kumpulan Abstrak Hasil Penelitian 1990-1991 Sekolah Tinggi Seni Indonesia (STSI) Surakarta and informants. The research data consists of words, phrases, and clauses in Kumpulan Abstrak Hasil Penelitian (KAHP) 1990-1991 Sekolah Tinggi Seni Indonesia (STSI) Surakarta and its translation in English and the raters’ statements about the accuracy and acceptability levels of translation. The research data were collected with document analysis, questionnaires, and interview. Findings of the research show the following. First, there are 13 techniques used in the translation. 5 of them are included in mandatory techniques while the optional techniques include 12 techniques. It can be seen from the findings that 4 techniques belong to mandatory as well as optional techniques. Based on the quality analysis, it can be found that there are 9 techniques positively influence the translation accuracy and 11 techniques positively influence the translation acceptability. Thus, it can be concluded that, generally, the accuracy and acceptability of the translation are included in high level.